2018
DOI: 10.1103/physrevd.97.044036
|View full text |Cite
|
Sign up to set email alerts
|

Disks around merging binary black holes: From GW150914 to supermassive black holes

Abstract: We perform magnetohydrodynamic simulations in full general relativity of disk accretion onto nonspinning black hole binaries with mass ratio = 29/36. We survey different disk models which differ in their scale height, total size and magnetic field to quantify the robustness of previous simulations on the initial disk model. Scaling our simulations to LIGO GW150914 we find that such systems could explain possible gravitational wave and electromagnetic counterparts such as the Fermi GBM hard x-ray signal reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 99 publications
5
50
2
Order By: Relevance
“…If we suppose that µ = 10 −14 µ B [41], where µ B is the Bohr magneton, then the magnetic field should be in the range (10 3 −10 7 ) G. Even if we take that µ ∼ 10 −19 µ B [42], which is a natural value for a Dirac neutrino with the mass ∼ 1 eV [43], the magnetic field should be as strong as (10 8 − 10 12 ) G. Such magnetic fields are compatible with the results of the numerical simulations of accretion disks carried out in Ref. [39], where B ∼ 10 12 G was used.…”
Section: Neutrino Spin Oscillations In a Gravitational Wavesupporting
confidence: 82%
See 2 more Smart Citations
“…If we suppose that µ = 10 −14 µ B [41], where µ B is the Bohr magneton, then the magnetic field should be in the range (10 3 −10 7 ) G. Even if we take that µ ∼ 10 −19 µ B [42], which is a natural value for a Dirac neutrino with the mass ∼ 1 eV [43], the magnetic field should be as strong as (10 8 − 10 12 ) G. Such magnetic fields are compatible with the results of the numerical simulations of accretion disks carried out in Ref. [39], where B ∼ 10 12 G was used.…”
Section: Neutrino Spin Oscillations In a Gravitational Wavesupporting
confidence: 82%
“…The inner radius of such a disk was found in Ref. [39] to be ∼ 10R S = 10 8 cm, which is comparable with z 0 .…”
Section: Neutrino Spin Oscillations In a Gravitational Wavementioning
confidence: 53%
See 1 more Smart Citation
“…Other theories include the triggered collapse of a massive star due to its black hole companion (Janiuk et al 2017), and the fragmentation of the stellar core of a massive star (Loeb 2016; although see Dai et al 2017 andFedrow et al 2017). Lyutikov (2016) has argued that the physical properties necessary to create GW150914-GBM are highly implausible, although Khan et al (2018) surveyed different models of disks around merging BBHs using magnetohydrodynamic simulations and shows that such systems could produce an EM counterpart consistent with the properties of GW150914-GBM. Likewise Veres et al (2016) showed that dissipative photosphere models of GRB emission can accommodate the GBM observations.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the energy source could be entirely of eletromagnetic nature if the BHs are charged (Liebling & Palenzuela 2016;Zhang 2016;Liu et al 2016;Fraschetti 2018). GRMHD simulations have additionally demonstrated that jets are produced from merging BHs if there is some matter around the BHs at the time of merger (Khan et al 2018).…”
Section: Introductionmentioning
confidence: 99%